Uric acid-induced cardiomyocytic polyamines’ insufficience: a potential mechanism mediates cardiomyocytic injury - Lin, Cuiting; Zheng, Qiang; Yu, Haiyan; Wu, Ting; Chen, Lin; Lin, Weihao; Pang, Jianxin; Yang, Yang (Frontiers in Endocrinology, 2025)
IntroductionMaintaining polyamines homeostasis is essential for cardiovascular health, whereas elevated uric acid levels are recognized as a significant risk factor for the onset and progression of cardiovascular diseases. However, the interaction between uric acid and the regulation of polyamine homeostasis has not been extensively investigated. The objective of this study was to investigate the influence of uric acid on cardiac polyamines regulation and elucidate the role of polyamines in uric acid induced cardiomyocytic injury.MethodsThe in vitro experiments utilized H9C2 cardiomyocytes, the hyperuricemic mouse model was established via potassium oxonate and hypoxanthine. Techniques included energy metabolomics, HPLC for polyamine quantification, qPCR, ELISA, immunofluorescence, and mitochondrial membrane potential assessment using JC-1 staining, MTT cell viability analysis. ResultsUric acid treatment can alter ornithine metabolism in cardiomyocytes, revealed a potential of shifting it from the traditional ornithine cycle towards the polyamine cycle. Both ODC1 and SAT1 protein levels were up-regulated in hyperuricemic mice indicated a dysorder of polyamines homostasis. A downregulation tendency of spermidine and spermine levels were observed in cardiomyocytes under uric acid treatment. Notably, exogenous supplementation with spermidine or spermine effectively mitigated the uric acid-induced decline in cardiomyocyte viability and mitochondrial membrane potential.DiscussionUric acid disrupts polyamine homeostasis, leading to mitochondrial dysfunction and cardiomyocyte damage. Exogenous polyamine supplementation demonstrates therapeutic potential by preserving mitochondrial integrity. These findings unveil a potential mechanism underlying uric acid-induced cardiac injury and propose polyamine replenishment as a viable intervention strategy for hyperuricemia-related cardiovascular complications.